PERAN DAN KONTRIBUSI ALUMNI PONDOK PESANTREN DAARUL RAHMAN JAKARTA DALAM PERTUMBUHAN DAN PERKEMBANGAN PESANTREN DI JABOTABEK - Zaenal Jaenudin; Ahmad Munir Romdhoni Romdhon (Institut Binamadani Indonesia, 2026)
Daarul Rahman Islamic Boarding School is one of the largest Boarding Schools in DKI Jakarta, with thousands of former students spread across Indonesia. IKDAR (Daarul Rahman Family Association), as the former students' organization of the pesantren, which has evolved into a diaspora and expanded its institutional presence in Jabodetabek and various regions, represents a significant potential for developing institutional resilience capable of adapting to urban dynamics without abandoning the traditions of Ahlus Sunnah Waljamaah (Aswaja). The data analysis technique used in this research involves collecting secondary data, exposition, and conclusion through a qualitative approach. The research results show concrete contributions to the development of pesantren education in the Jabodetabek area through the role of IKDAR, which are as follows: curriculum, ulama cadre formation, self-sufficiency, and strengthening digital technology. The opportunity for the development of transformation at Daarul Rahman Islamic boarding school is very open, because the boarding school is a cultural stronghold that is integrated with the community, so the transformation of the boarding school will bring positive impacts on religious, social, and economic values for the community.